Seed Metabolism and Pathogen Resistance Enhancement in Pisum sativum During Colonization of Arbuscular Mycorrhizal Fungi: An Integrative Metabolomics-Proteomics Approach - Ranjbar Sistani, Nima; Desalegn, Getinet; Kaul, Hans-Peter; Wienkoop, Stefanie (Frontiers in Plant Science, 2020)
Pulses are one of the most important categories of food plants, and Pea (Pisum sativum L.) as a member of pulses is considered a key crop for food and feed and sustainable agriculture. Integrative multi-omics and microsymbiont impact studies on the plant's immune system are important steps towards more productive and tolerant food plants and thus will help to find solutions against food poverty. Didymella pinodes is a main fungal pathogen of pea plants. Arbuscular mycorrhizal fungi (AMF) promote plant growth and alleviate various stresses. However, it remained unclear as to how the AMF effect on seed metabolism and how this influences resistance against the pathogen. This study assesses the AMF impacts on yield components and seed quality upon D. pinodes infection on two different P. sativum cultivars, susceptible versus tolerant, grown in pots through phenotypic and seed molecular analyses. We found that AMF symbiosis affects the majority of all tested yield components as well as a reduction of disease severity in both cultivars. Seeds of mycorrhizal pea plants showed strong responses of secondary metabolites with nutritional, medicinal, and pharmaceutical attributes, also involved in pathogen response. This is further supported by proteomic data, functionally determining those primary and secondary metabolic pathways, involved in pathogen response and induced upon AMF-colonization. The data also revealed cultivar specific effects of AMF symbiosis that increase understanding of genotype related differences. Additionally, a suite of proteins and secondary metabolites are presented, induced in seeds of P. sativum upon AMF-colonization and pathogen attack, and possibly involved in induced systemic resistance against D. pinodes, useful for modern breeding strategies implementing microsymbionts towards increased pathogen resistance.